O protagonismo de imigrantes bolivianos em São Paulo: condicionantes e possibilidades - Farias, Júnior César Oliveira (Universidade Federal de São Carlos, 2020)
This work aims to describe and analyze contemporary collective actions of Bolivian immigrants in the search for social, cultural, political, and economic rights, in the city of São Paulo. In the 2000s, mainly in the 2010s, the capital of São Paulo experienced the emergence of immigrant collectives that, together with former organizations, began to seek immigrants’ protagonism in the face of their struggles and demands. With this scenario in mind, we intend to answer the following question: to what extent are the struggles for rights fought by Bolivians representative of a new emancipatory paradigm for immigrants? To achieve this objective, the investigation made use of an ethnographic approach, with interviews with activists who lead immigrant mobilizations in São Paulo, observations at events and public manifestations by Bolivian immigrants, observation on social networking of collectives of Bolivian immigrants, beyond bibliographic reading. It tries to analyze the relationship of these actions (and theirs agents) with the State and public policies, through the concept of “political opportunities and constraints” (Tilly, 2008; Tarrow, 2009). In this regard, we expect that the results can serve as a parameter and a contribution for those who hope to reflect about other situations of collective actions undertaken by immigrants, whether they are Bolivians or not.
The protagonism of Bolivian immigrants in São Paulo: conditions and possibilities
Keywords: Imigrantes; Bolivianos; Ações coletivas; Mobilizações políticas; São Paulo; Immigrants; Bolivians; Collective actions; Political mobilization; CIENCIAS HUMANAS::SOCIOLOGIA